Cultural Narratives: Celebrity Sports as a Heroic Reference of our Time: The sports brand Nike and its Instagram account - Díaz-Bajo Rodríguez, Javier; Martínez Borda, Rut; Lacasa Díaz, Pilar (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Advertising discourses are conceived as processes of production of meaning and symbolic significance that establish socially and culturally. The objectives of our study are based on interpreting the latent mythical foundations that are present in the discursive representation evoked by the Nike corporation. The methodology used is based on Norman Fairclough's critical discourse analysis and the multimodal discourse analysis approach. The conclusions corroborate that the sports celebrity acts as a cultural artifact that instrumentalizes the imaginary of the brand based on the social realities of our time.